2020
DOI: 10.1071/cp18369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilisation and irrigation on seed yield and yield components of signal grass (Urochloa decumbens)

Abstract: The effects of nitrogen (N) fertiliser rate and irrigation on seed yield and its components were evaluated for signal grass (Urochloa decumbens (Stapf) R.D. Webster; syn. of Brachiaria decumbens Stapf) cv. Basilisk in a field experiment in Umuarama, Paraná, Brazil. Two water regimes (irrigated and non-irrigated) and four nitrogen (N) fertiliser rates (0, 25, 50 and 75 kg ha–1) were applied to perennial signal grass crops in a split-plot randomised complete block design with three replications. In two consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
2
4
2
1
Order By: Relevance
“…The heading number of Zoysia japonica, Agropyron cristatum, and Psathyrostachys juncea increases significantly under a suitable level of N application (Tandoh et al, 2019;Qasim et al, 2020;Zanon et al, 2020). However, our findings are inconsistent with a previous study conducted in Brazil showing that the seed yield of grass was not greatly affected by water (Canto et al, 2020).…”
Section: Seed Yieldcontrasting
confidence: 93%
“…The heading number of Zoysia japonica, Agropyron cristatum, and Psathyrostachys juncea increases significantly under a suitable level of N application (Tandoh et al, 2019;Qasim et al, 2020;Zanon et al, 2020). However, our findings are inconsistent with a previous study conducted in Brazil showing that the seed yield of grass was not greatly affected by water (Canto et al, 2020).…”
Section: Seed Yieldcontrasting
confidence: 93%
“…The N-rate of 150 kg N/ha produced approximately 16% more TN than the control treatment. Our results were similar to those obtained in previous studies on U. decumbens and U. ruziziensis, which showed that TN increased with an increase in the N-rate [20,21]. Wongsuwan [18] also found that the addition of 150 and 250 kg N/ha significantly increased total reproductive tiller numbers.…”
Section: Soil and Weather Conditionssupporting
confidence: 92%
“…These studies found that the optimal N-rate varied from 40 kg/ha to 400 kg/ha due to several factors, such as soil nutrients, including N, soil moisture, changes in environmental parameters that affect crop development, and other aspects related to crop management. Research groups in different countries have undertaken studies on Urochloa; for example, in Brazil, studies have been conducted on U. brizantha [20] and U. decumbens [21], and in Benin, on U. ruziziensis [22]. Their results showed that N-rates for seed production ranged from 50 kg/ha to 100 kg/ha.…”
Section: Introductionmentioning
confidence: 99%
“…Lighter dry matter yields were obtained from the unfertilized plants and those applied with 30 kg N ha -1 . The result is in conformity with the reported increase in plant biomass of signal grass (Canto et al, 2020) and dry matter yield of palisade grass (Dupas et al, 2016) with N fertilization.…”
Section: Fresh Herbage and Dry Matter Yieldssupporting
confidence: 91%
“…These corroborated the results of Silva et al (2013) who reported an increase in the number of vegetative tillers of marandu grass with N fertilization due to its positive effect on leaf elongation and tillering rate promoting greater capacity in the formation of axiliary buds, which may potentially originate new tillers. Likewise, Canto et al (2020) reported significant increase in reproductive tiller density of signal grass at harvest for the first and second crops with N fertilization.…”
Section: Agronomic Characteristicsmentioning
confidence: 88%